Hazard Identification, Risk Assessment and Risk Control (HIRARC) in Lifting Operations: A Case Study of Fall Incident at a High-Rise IBS Construction Project. - Nurdeana Qarmila Shamsuddin,; Aliff Hisyam A Razak,; Muhamad Firdous Basheer Ahmad, (Progress in Engineering Application and Technology, 2026)
Tower Crane lifting operations in high-rise Industrialized Building System (IBS) construction projects present significant occupational safety and health risks, particularlya those related to work at height and handling of heavy prefabricated components. Despite the importance of impelementation hazard identification, risk assessment and risk control (HIRARC) in Malaysia crane-related incidents continue to occur indicating potential weaknesses in practical implementation. This study aims to evaluate the effectiveness of HIRARC implementation during lifting operations through a case study of a fall incident involving a signalman during the installation of a Prefabricated Bathroom Unit (PBU) at a high-rise construction site. A qualitative case study approach was used which include reviewing the Method Statement and Job Safety Analysis, conducting semi-structured interviews with workers involved and carrying out site observations after the incident. The results show that even though hazards and control measures were identified in documents, there were major weaknesses in how they were applied on site. These included not following the approved work sequence, using an unstable temporary slab as a work platform, poor supervision and ineffective communication. These weaknesses caused a gap between the planned risk control measures and the actual conditions at the worksite. The study concludes that effective HIRARC implementation in real work settings requires more than written documentation alone; it demands continuous attention, strong supervision, and a high level of safety compliance in daily site activities. The findings offer practical recommendations to improve HIRARC practices and enhance safety performance in IBS lifting operations.